Efectos en la logística comercial de las pymes post-pandemia covid-19. - Espinoza Castillo, Ronny Alexander; Nieto Contreras, Patricio Xavier (My University, 2021)
The Covid-19 pandemic has affected the entire world economy causing great problems and social instability in countries. The business world has also been affected, as the economic activities of companies that were known as normal, have undergone drastic changes. The objective of this research is to determine the effects of commercial logistics on the market development of SMEs in the City of Machala post-Covid-19 pandemic. The research is qualitative and descriptive in nature, the research is non-experimental with a cross-sectional design. A survey was applied to 254 SMEs, resulting in few changes that the commercial logistics in the SMEs of Machala have undergone during the pandemic, as they are not transcendental. Taking into account the adoption of logistics strategies that are synchronized between SMEs and the market, the processes that will continue to be used post-pandemic are the relationship with suppliers, purchase planning and way of selling.
La pandemia por Covid-19 ha afectado a la economía del mundo entero causando grandes problemas e inestabilidad social en los países. El mundo empresarial también se ha visto afectado, pues actividades económicas de las empresas que se conocían como normales, han sufrido cambios drásticos. El objetivo de la presente investigación es determinar los efectos de la logística comercial en el desarrollo del mercado de las PYMES de la Ciudad de Machala post-pandemia Covid-19. La investigación es de carácter cualitativo de alcance descriptivo, la investigación es no experimental de diseño transversal. Se aplicó una encuesta a 254 pymes dando como resultado que, pocos son los cambios que ha sufrido la logística comercial en la Pymes de Machala durante la pandemia, pues no son trascendentales. Tomando en cuenta la adopción de estrategias logísticas que se sincronicen entre Pymes y el mercado, los procesos que se seguirán utilizando post-pandemia Covid-19 son la relación con los proveedores, planificación de compras y forma de vender.
Keywords: COVID-19; LOGÍSTICA COMERCIAL; PYMES